Evaluation of antioxidant potential of African Nutmeg (Monodora myristica) on the peroxide value of soya bean oil - Ukoha, O. A.; Onunkwo, D. N. (Nigerian Journal of Animal Science, 2023)
The antioxidative activity of African Nutmeg (Monodora myristica) was evaluated using ethanol extract of the spice in soya bean oil over a period of 28 days. The peroxide value was used to monitor the development of rancidity in the oil. The peroxide values of soya bean oil treated with 2.5ml, 5.0ml, 7.5ml and 10ml concentrations of the Monodora myristica were measured. The peroxide value of the 10ml Monodora myristica- treated soya bean oil was not raised (P<0.05) up to 20mg/g oil until about 21 days of storage. The peroxide value of the varying concentrations of Monodora myristica crude extract revealed that the quantity of peroxide generated increased with time. Between day 0 and day 7, the peroxide value of all the samples treated with the varying concentrations of the Monodora extracts and the control were low and were different (P<0.05) from one another. In the Monodora extracted oil, the peroxide value between this period and the 7th day were below 10mg/g oil while the control recorded 10.52mg/g oil. The peroxide values increased in all the samples above 10mg/g oil between the 14th day and 28th day. From the results, Monodora myristica appears to be effective in the improvement of the shelf life of soya bean oil and so promises to improve the shelf life of broiler feeds under storage